TRANSFORMATION OF CONSUMER (CLIENT) CAPITAL PROPERTIES THROUGH BEHAVIORAL MECHANISMS OF DIGITIZATION - HANNOUF, Katerina (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The research is dedicated to the transformation of consumer (client) capital as a component of intellectual capital, serving as an indicator of its sustainable development in the era of digitalization of economic processes. Research objective. The aim of the study lies in developing a methodological approach to the transformation of properties of intellectual capital through behavioral mechanisms of digitalization of economic processes and determining an index enabling tracking the influence of behavioral mechanisms on economic processes in real-time. Additionally, the paper refines and categorizes the components of consumer (client) capital, elucidates their essence, and proposes methodological approaches for determining the levels of individual components and the overall level of consumer (client) capital depending on behavioral mechanisms of economic processes. Furthermore, it identifies an index allowing tracking the impact of behavioral mechanisms of economic processes in real-time and comparing the economic efficiency of influencing enterprise activities. Methodology: The study employs dialectical method, analysis and synthesis (investigation of structural (client) capital and determination of its elements and qualitative characteristics of properties), graphical method (for illustrating research results), systemic-structural and expert analysis (for determining the impacts of changes in consumer capital properties and its qualitative characteristics and influences on the effectiveness of socio-economic systems). Scientific novelty lies in the development of a methodological approach to the transformation of consumer capital properties through behavioral mechanisms of economic process digitization and determining an index enabling tracking the impact of behavioral mechanisms of economic processes in real-time and influencing the optimization of the structure of intellectual capital of socio-economic systems. Practical significance involves recommending a methodological approach to transforming consumer (client) capital properties through behavioral mechanisms of economic process digitization and an index for comparing the economic efficiency of influencing company activities with general possibilities of using other mechanisms.